A random coincidence point theorem for multifunction - Fakhar, Kamran; Mustafa, Ghulam; Azram, Mohammad (Academic Publications, Ltd., 2010)
A random coincidence point theorem for multifunction under the very mild conditions is established. The theorem proved here can be viewed as stochastic version of Ljubomir Ciric (Indian J. pure appl. Math., 24 (1993),145-149).